THE EFFECT OF ADDITION OF BLACK TIN (Pb) IN BRONZE ALLOYS WITH HIGH TIN CONTENT ON IMPACT STRENGTH AND MICROSTRUCTURE - Fahrezi, Michael (ROTOR, 2025)
High-tin bronze (CuSn), especially with tin content above 17%, is commonly used in industries for making gamelan and bells due to its excellent acoustic properties. However, this alloy has drawbacks such as high cost and brittleness, which can cause cracking during forging and use. This study investigates the effect of adding lead (Pb) on the impact strength and microstructure of high-tin bronze alloys. Lead was chosen because it is cheaper than tin, helps reduce porosity, and can improve mechanical properties. Variations of Pb added were 5%, 10%, and 15%. The impact strength was tested using the Charpy impact test, and the microstructure was examined with a metallurgical microscope. Results showed that adding Pb improved the impact strength, with the composition of 80% Cu, 20% Sn, and 10% Pb achieving the highest impact strength of 0.0274 Joule/mm², compared to 0.0164 Joule/mm² in the pure alloy. The 10% Pb addition also created a uniform Pb distribution. However, adding more than 10% Pb reduced the impact strength, making the alloy less optimal. Therefore, 10% Pb provided the best balance between mechanical performance and microstructure. Keywords: Copper (Cu), white tin (Sn), lead (Pb), impact, microstructure